The Problems of Reviewing the Audit Report of the Financial Audit Board - Pundhilaras, Rindhang; Eka Yuniza, Mailinda (Fakultas Hukum Universitas Gadjah Mada, 2025)
The judiciary has diverse decisions regarding on their competence to review the Audit Report of the Financial Audit Board (the LHP BPK). Some of judges in ordinary courts regarded that the LHP BPK falls in the competence of Administrative Courts; however, some judges of Administrative Courts regarded that the LHP BPK is not similar to an administrative decision; so that, they decline to review the LHP BPK. Therefore, this paper aims to evaluate where and how should the LHP BPK be reviewed This study uses a normative juridical research method using secondary data in the form of regulations, books, articles, research, and journals to analyze the position of the LHP BPK as a form of implementing the duties, functions, and authority of BPK as an independent institution. This research finds that the problematic situations occur because of legal loopholes due to the silent of the Law. Legislature therefore needs to promulgate norms on the matter. Meanwhile this study offer some temporary solutions to mitigate the loopholes.